1997
DOI: 10.1016/s0741-5214(97)70321-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical follow-up rather than duplex surveillance after carotid endarterectomy

Abstract: After carotid endarterectomy restenosis is rarely associated with symptoms; contralateral stroke is rare and is not associated with progressive internal carotid artery disease suitable for endarterectomy. This study has shown no benefit from long-term duplex surveillance after carotid endarterectomy. Selective clinical follow-up of patients who have high-grade contralateral stenoses would appear more appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
1
29
1
2
Order By: Relevance
“…2 Golledge et al 1 recommended restriction of follow-up to those with ≥50% stenosis, as this protocol will reduce CDUS surveillance by 78%. Another review by Golledge et al indicated a very low yield of CDUS surveillance after CEA, with only 13 patients (5.9%) with severe disease warranting additional intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Golledge et al 1 recommended restriction of follow-up to those with ≥50% stenosis, as this protocol will reduce CDUS surveillance by 78%. Another review by Golledge et al indicated a very low yield of CDUS surveillance after CEA, with only 13 patients (5.9%) with severe disease warranting additional intervention.…”
Section: Discussionmentioning
confidence: 99%
“…1-5 Advancements in medical treatment and the current emphasis on cost-effectiveness have questioned the value of performing routine carotid ultrasound scanning after CEA.…”
mentioning
confidence: 99%
“…This may result from special morphology of early restenosis (myointimal hyperplasia) which has evidently low embolic potential. However, the development of typical atherosclerotic plaques is often on later stages of restenosis [15][16][17]. Thus, rate of cerebrovascular complications may be different in patients with early and later restenosis [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the embolization as the etiology of most strokes is that few infarcts are in watershed areas [24], microemboli can be detected in the middle cerebral artery [25], and stenosis or restenosis of similar hemodynamic severity are much less likely to be associated with stroke when asymptomatic plaque is present [5,6,26]. Furthermore, Marcus et al, [27] reported that the frequency of embolization on transcranial Doppler is greater in patients with recent symptoms, such as transient ischemic attack, when compared with patients with similar severe asymptomatic disease.…”
Section: Mechanism Of Stroke In Carotid Artery Diseasementioning
confidence: 99%